The Contribution of Communication Skills and Digital Literacy to Students’ Critical Thinking Skills - Astuti Muh. Amin; Romi Adiansyah (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2023)
Past studies rarely reported the contribution of communication skills and digital literacy to students’ critical thinking skills in biology. The present study identified the correlation between communication and digital literacy skills and its contribution to students’ critical thinking skills by implementing three learning models. This study employed a correlational research design and involved all biology education students in Ternate, North Maluku, Indonesia. The research sample included 60 students from IAIN Ternate and STIKIP Kie Raha, Ternate. The study was conducted in the even semester of the 2021/2022 academic year. Data were gathered using a questionnaire, observation sheets, and an essay test. Multiple linear regression analysis showed the simultaneous contribution of communication and digital literacy to critical thinking in the WE-ARe classroom (73.3%); STAD (63.6%); and conventional (50.4%). These results suggest that the contribution of the predictors to critical thinking was higher in the WE-ARe class than in STAD or conventional classes